PEMBELAJARAN KONTRUKTIFISTIK DENGAN PENDEKATAN CTL PADA TEORI BELAJAR BERMAIN DIENES - Rahman, Hairur (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2009)
In order to improve the studentsâ€™ mastering at elementary schools, it is important to note that the teaching strategies should not be only focused on â€œhow to teachâ€, however the teaching should be also focused on â€œhow to stimulateâ€ and â€œhow to learnâ€.Â  In this context, the contextual teaching and learning approach (CTL) is considered as the new approach, particularly for math subject, which has been applied in Indonesia. For this purpose, this article offers the concept teaching model by Dienes theory using CTL approach.Kata Kunci: CTL, Konstruktivisme, Teori Belajar Bermain Dienes.Â  Â